Comparison of pressing methods and varieties to produce virgin poppy (Papaver somniferum L.) oil for nutraceutical use - Katalin Gupcsó; Éva Zámboriné Németh (Applied Food Research)
The use of poppy seeds and oil are increasing because of their high nutraceutical value. The goal of the presented study was to reveal the recovery rate and fatty acid composition of poppy seed oil obtained by different extraction methods (cold and warm pressing, screw press) of four varieties from two vegetation years.We established, that the oil point of the samples varied between 1.42 – 2.13 MPa in the pressing methods depending on variety and year. The extraction method has significant effect on the oil yield (24.72–43.43 ml/100 g seeds) and on the oil content of the flour (13.0–35.0 % d.w.). The best recovery rate could be achieved by the screw press method (64.25 %) and the lowest one by the cold pressing (24.81 %). However, the effect of the variety and the vegetation year was also significant on these values.Screw method assured the highest polyunsaturated fatty acid ratio (linolic, α-linoleic and eicosadienoic acids) in parallel with a decrease of the saturated and monounsaturated fatty acid fractions. However, the differences could not be ascertained statistically. Concerning the oil quality, the variety was the determinant factor. Significant variations among them were determined for each fatty acid fractions in both years. The study demonstrated that both the poppy variety and the pressing method should be optimised to produce high amount of poppy oil with acceptable composition.